RECOGNITION OF A PSYCHOEMOTIONAL STATE BASED ON VIDEO SURVEILLANCE: REVIEW (Journal of Mathematics Mechanics and Computer Science, 2021)
Currently, the determination of the psychoemotional state of the observed, including students and pupils, is an urgent task that has social significance. The pace of technology development and the increased interest of foreign and domestic specialists show that the automation of the determination of psychoemotional reactions is an actual and popular area of research. The article provides an overview of various literature sources on this topic, analyzes the existing types of emotional artificial intelligence that allow a computer to recognize and interpret human emotions and respond to them. The camera reads the person's state, and the neural network processes the data to determine the emotion. In addition, recent research papers published during 2019 and 2020 are included to present the latest advances in this field.
Keywords: Computer vision; image processing; cluster analysis; signal processing; neural network; filtering